Expression of FoxC, FoxF, FoxL1, and FoxQ1 genes in the dogfish Scyliorhinus canicula defines ancient and derived roles for Fox genes in vertebrate development. - Wotton, K; Mazet, F; Shimeld, S (2008)
In the human genome, members of the FoxC, FoxF, FoxL1, and FoxQ1 gene families are found in two paralagous clusters. Here we characterize all four gene families in the dogfish Scyliorhinus canicula, a member of the cartilaginous fish lineage that diverged before the radiation of osteichthyan vertebrates. We identify two FoxC genes, two FoxF genes, and single FoxQ1 and FoxL1 genes, demonstrating cluster duplication preceded the radiation of gnathostomes. The expression of all six genes was analyzed by in situ hybridization. The results show conserved expression of FoxL1, FoxF, and FoxC genes in different compartments of the mesoderm and of FoxQ1 in pharyngeal endoderm and its derivatives, confirming these as ancient sites of Fox gene expression, and also illustrate multiple cases of lineage-specific expression domains. Comparison to invertebrate chordates shows that the majority of conserved vertebrate expression domains mark tissues that are part of the primitive chordate body plan.